Lasting progress of the public schools - Morgan, Arthur Houston (My University, 1896)
Introduction: The question of public schools is one that interests the people of our land more than any other subject. The schooling of 85% of our population never goes beyond that gained in the public school. No other organization has a greater influence on civilization. His progress has been rapid and its influence has been lasting.
Citation: Morgan, Arthur Houston. Lasting progress of the public schools. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Public schools; Civilization; Schooling; Theses; Manuscripts (documents)